Pendidikan Agama Islam Inklusif-Multikultural - Imam Bahrozi (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2018)
Islam is as a universal religion, as a religion for humanity (all humankind), or as a religion for the entire world because of its’ mission as rahmatan li al-’alamin. To realize such mission in Indonesian context, education activity is aimed to raise up a multicultural wisdom and global awareness of the pupils, so in next time they will be able to contribute in preservation of heterogenity and to develop it for attaining a prosperious life, besides to face globalization current appropiately. In this case, islamic education has a duty in transfering inclusive-multiculturalism Islamic teachings to students so that they are able to appreciate global values of Islam, like inclusivism, humanism, tolerance, and democracy.